2008
DOI: 10.1111/j.1745-4565.2007.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF LACTOBACILLUS SAKEI AND STAPHYLOCOCCUS XYLOSUS ON THE INHIBITION OF ESCHERICHIA COLI O157:H7 IN PASTIRMA, A DRY‐CURED MEAT PRODUCT

Abstract: Pastırma was produced from beef meat contaminated with Escherichia coli O157:H7 to investigate the effects of protective cultures on the behavior of E. coli O157:H7 in pastırma manufacturing. After being contaminated with E. coli O157:H7 (105 cfu/g), meats for pastırma were divided into two groups. The control group was untreated meat, and the treatment group was meat in which protective cultures (Lactobacillus sakei + Staphylococcus xylosus) were added. E. coli O157:H7 was decreased during processing and show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…These bacteria can be effective in the reduction of nitrate to nitrite and in the formation of the desired colour and flavour (Katsaras et al ., 1996). The change in LAB counts in various studies carried out on pastırma was parallel to the present research findings (3-5 Log CFU/g) (Aksu and Kaya, 2002c; Aksu et al ., 2008; Christensen et al ., 2000; DuBose et al ., 1981; Gurbuz et al ., 1995). In the researches carried out, M-Y count in pastırma was indicated as < 10 2 to 10 6 CFU/g (Aksu and Kaya, 2002c; Dogruer et al ., 2003; Elmali et al ., 2007; Gurbuz et al ., 1995).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These bacteria can be effective in the reduction of nitrate to nitrite and in the formation of the desired colour and flavour (Katsaras et al ., 1996). The change in LAB counts in various studies carried out on pastırma was parallel to the present research findings (3-5 Log CFU/g) (Aksu and Kaya, 2002c; Aksu et al ., 2008; Christensen et al ., 2000; DuBose et al ., 1981; Gurbuz et al ., 1995). In the researches carried out, M-Y count in pastırma was indicated as < 10 2 to 10 6 CFU/g (Aksu and Kaya, 2002c; Dogruer et al ., 2003; Elmali et al ., 2007; Gurbuz et al ., 1995).…”
Section: Discussionsupporting
confidence: 88%
“…Micrococcus and Staphylococcus were dominated in pastırma microflora because of its resistant to high salt concentration (Aksu and Kaya, 2002b; Kaban, 2009). The M/S number was explained between 10 3 and 10 7 CFU/g in the studies (Aksu and Kaya, 2001b; Aksu and Kaya, 2002a, Aksu and Kaya, 2002b; Aksu et al ., 2008; DuBose et al ., 1981; Elmali et al ., 2007). Micrococcus and Staphylcoccus that can develop in aerobic or very low-oxygen environments are the dominant bacteria group in the pastırma and are very important bacteria in the formation of the desired quality of pastırma.…”
Section: Discussionmentioning
confidence: 93%
“…Doǧruer et al 28 determined that pH value of the pastirma ranged from 5.56 to 6.54 (average 5.88). Aksu et al 29 determined that the pH value in pastirma was 5.66.…”
Section: Resultsmentioning
confidence: 99%
“…sakei and Staph. xylosus in pastirma have demonstrated that the most significant reduction in the counts of the pathogen was recorded after the drying step regardless of whether or not the protective cultures were present (Aksu and others ). Similar results were reported for Moroccan gueddid where numbers of TAC, coliforms, and staphylococci showed a dramatic decrease after the maturation step to reach an undetectable level in a 1 g sample for coliforms and staphylococci, and about 40 CFU/g for TAC (Kalalou and others ).…”
Section: Microbiology Of Traditional North African Foods and Associatmentioning
confidence: 98%